A lithium-ion battery silicon-based negative electrode material and its preparation method and application

By using a negative electrode material doped with lithium nanoparticles in the silicon carbon matrix and a polymerized carbonization layer in lithium-ion batteries, the problems of powderization and capacity reduction caused by volume changes in the silicon negative electrode material are solved, and higher energy density and cycling stability are achieved.

CN119133422BActive Publication Date: 2025-03-18NANCHANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411635639.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-18
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The theoretical specific capacity of traditional graphite anode materials for lithium-ion batteries is low, which is difficult to meet the needs of high energy density. At the same time, the huge volume changes of silicon anode materials during charging and discharging lead to pulverization and peeling of active materials, resulting in a decrease in capacity or failure.

Method used

A lithium-ion silicon-based anode material is used, which includes a silicon-carbon matrix and doped in situ reduced lithium nanoparticles in the polymerized carbonized layer on the surface of the silicon-carbon matrix. The silicon-carbon matrix forms a stable silicon-carbon framework by interwoven with the polymerized carbonization layer. The polymerized carbonization layer protects the silicon-carbon matrix, and the lithium nanoparticles provide additional lithium sources and active sites.

Benefits of technology

It effectively suppresses the volume expansion of silicon material, improves the structural stability of the negative electrode material, and enhances the cycle stability and rate performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133422B_ABST
    Figure CN119133422B_ABST
Patent Text Reader

Abstract

The present invention provides a lithium-ion battery silicon-based negative electrode material and a preparation method and application thereof, and relates to the technical field of lithium-ion battery negative electrode materials. The preparation method provided by the present invention comprises stirring and mixing a surface-activated silicon-carbon matrix in an organic solution in which a polymer is dissolved, and then separating and drying to obtain a composite matrix; mixing the composite matrix in an inorganic lithium salt solution, evaporating the solvent, and carbonizing at 300°C-400°C to obtain a composite intermediate; reducing the composite intermediate under a hydrogen atmosphere of 200°C-300°C to obtain a negative electrode intermediate; stirring and mixing the negative electrode intermediate in the organic solution, separating and drying, and carbonizing at 700°C-800°C to obtain a lithium-ion battery silicon-based negative electrode material. The negative electrode material prepared by the present invention has high structural stability, and after being applied to a lithium-ion battery, it can significantly improve the capacity performance and cycle stability of the lithium-ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery negative electrode materials, and in particular to a lithium ion silicon-based negative electrode material and a preparation method and application thereof. Background Art

[0002] Among the numerous energy storage technologies, lithium-ion batteries are widely used in electronic equipment, electric vehicles, etc. due to their high energy density, high output power, high operating voltage, no memory effect, long cycle life, etc. However, with the rapid development of electronic energy-demanding equipment, the requirements for the energy density of lithium-ion batteries are getting higher and higher, while the theoretical specific capacity of traditional graphite negative electrode materials for lithium-ion batteries is only 372mAh / g, which is difficult to meet the existing demand.

[0003] The theoretical specific capacity of silicon is as high as 4200mAh / g, which is the negative electrode material with the highest theoretical capacity to date. Using silicon material as a lithium-ion negative electrode material can effectively improve the energy density of lithium-ion batteries. However, the silicon negative electrode is accompanied by huge volume changes during the charging and discharging process, and its volume expansion rate is as high as 270%. The pulverization caused by the volume change of silicon material causes the active material to peel off, and ultimately leads to a significant decrease in the capacity of the lithium-ion negative electrode or even complete failure. Therefore, it is urgent to provide a solution to inhibit the volume expansion of silicon materials and improve the structural stability of negative electrode materials, which is of great significance for improving the coulombic efficiency and cycle stability of lithium-ion batteries. Summary of the invention

[0004] The object of the present invention is to provide a lithium ion silicon-based negative electrode material and a preparation method and application thereof.

[0005] In a first aspect, the present invention provides a method for preparing a silicon-based negative electrode material for a lithium-ion battery, comprising the following steps: stirring and mixing a surface-activated silicon-carbon matrix in an organic solution containing a polymer, separating and drying to obtain a composite matrix; mixing the composite matrix in an inorganic lithium salt solution, evaporating the solvent, and carbonizing at 300°C-400°C to obtain a composite intermediate; reducing the composite intermediate under a hydrogen atmosphere at 200°C-300°C to obtain a negative electrode intermediate; stirring and mixing the negative electrode intermediate in the organic solution, separating and drying, and carbonizing at 700°C-800°C to obtain a silicon-based negative electrode material for a lithium-ion battery.

[0006] Optionally, nano silicon powder is mixed with a carbon precursor in advance, ball-milled and calcined to obtain a silicon-carbon matrix.

[0007] Optionally, the mass ratio of the nano-silicon powder to the carbon precursor is 1:(5-6).

[0008] Optionally, the particle size of the nano silicon powder is 50nm-150nm.

[0009] Optionally, the carbon precursor includes one of phenolic resin, asphalt, and glucose.

[0010] Optionally, the nano-silicon powder and the carbon precursor are mixed and ball-milled at 100° C.-200° C.

[0011] Optionally, the nano silicon powder is mixed with the carbon precursor and ball-milled for 8 h to 10 h.

[0012] Optionally, the nano-silicon powder and the carbon precursor are mixed and ball-milled, and then calcined at 700° C.-1000° C. to obtain a silicon-carbon matrix.

[0013] Optionally, the particle size of the silicon carbon matrix is ​​50nm-100nm.

[0014] Optionally, the silicon-carbon substrate is surface-treated in a silane solution in advance to obtain a surface-activated silicon-carbon substrate.

[0015] Optionally, the solid-to-liquid ratio of the silicon-carbon matrix to the silane solution is 0.05 g / mL-0.08 g / mL.

[0016] Optionally, the mass ratio of the silane solute in the silane solution to the silicon-carbon matrix is ​​(0.20-0.25):1.

[0017] Optionally, the silane solute in the silane solution includes one of KH-550, KH-560, and KH-570.

[0018] Optionally, the silicon carbon substrate is surface treated in a silane solution at 50° C.-60° C.

[0019] Optionally, the silicon carbon matrix is ​​dispersed in a silane solution by ultrasonication.

[0020] Optionally, the mass ratio of the surface activated silicon-carbon matrix to the polymer is 1:(0.1-0.3).

[0021] Optionally, the polymer includes at least one of melamine, polypyrrole and polyaniline.

[0022] Optionally, the solvent in the organic solution includes one of dimethyl sulfoxide, N,N-dimethylformamide and dimethylformamide.

[0023] Optionally, the surface-activated silicon-carbon matrix is ​​ultrasonically mixed with an organic solution containing a polymer.

[0024] Optionally, the surface activated silicon carbon matrix is ​​stirred and mixed in an organic solution at 45° C.-55° C.

[0025] Optionally, the mass ratio of the composite matrix to the lithium solute in the inorganic lithium salt solution is 1:(0.08-0.12).

[0026] Optionally, the lithium solute in the inorganic lithium salt solution includes one of lithium hydroxide and lithium hexafluoroarsenate.

[0027] Optionally, the solid-to-liquid ratio of the composite matrix to the inorganic lithium salt solution is 0.05 g / mL-0.08 g / mL.

[0028] Optionally, the composite matrix is ​​mixed in an inorganic lithium salt solution at 50°C-60°C.

[0029] Optionally, the composite matrix is ​​ultrasonically mixed in the inorganic lithium salt solution.

[0030] Optionally, the composite matrix is ​​mixed in an inorganic lithium salt solution, the solvent is evaporated, and deionized water is used for circulating flushing.

[0031] Optionally, after the solvent is evaporated, carbonization is performed at 300° C.-400° C. in a non-oxidizing atmosphere, wherein the non-oxidizing atmosphere includes one of a nitrogen atmosphere and an inert atmosphere.

[0032] Optionally, after the solvent is evaporated, the temperature is raised to 300° C.-400° C. at a rate of 1° C. / min-10° C. / min.

[0033] Optionally, after the solvent is evaporated, the carbonization treatment is performed at 300° C.-400° C. for 5 h-6 h.

[0034] Optionally, the composite intermediate is heated to 200° C.-300° C. at a rate of 1° C. / min-10° C. / min under a hydrogen atmosphere.

[0035] Optionally, the composite intermediate is kept under hydrogen atmosphere for 2 h-3 h.

[0036] In a second aspect, the present invention further provides a silicon-based negative electrode material prepared by any of the above optional preparation methods.

[0037] In a third aspect, the present invention also provides the use of the silicon-based negative electrode material prepared by any of the above optional preparation methods in a lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The present invention provides a flow chart of a method for preparing a silicon-based negative electrode material for a lithium-ion battery. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0040] The present invention provides a silicon-based negative electrode material for a lithium-ion battery, comprising a silicon-carbon matrix and a polymerized carbonized layer formed on the surface of the silicon-carbon matrix, wherein the polymerized carbonized layer is doped with in-situ reduced lithium nanoparticles; the silicon-carbon matrix has a silicon-carbon skeleton interwoven with the polymerized carbonized layer.

[0041] In fact, the silicon-carbon matrix can effectively alleviate the volume expansion of silicon and improve the overall conductivity of the negative electrode material, which is important for improving the cycle stability and rate performance of lithium-ion batteries. The polymerized carbonized layer on the surface of the silicon-carbon matrix can protect the silicon-carbon matrix, prevent the electrolyte from excessively corroding the silicon-carbon matrix, and reduce the occurrence of side reactions. In addition, the polymerized carbonized layer can further improve the structural stability of the silicon-carbon matrix and inhibit the damage caused by the volume expansion of silicon in the silicon-carbon matrix. At the same time, the silicon-carbon skeleton in the silicon-carbon matrix is ​​intertwined with the polymerized carbonized layer, which can effectively improve the connection stability between the polymerized carbonized layer and the silicon-carbon matrix, thereby improving the protection effect of the silicon-carbon matrix.

[0042] In fact, the lithium nanoparticles in the polymerized carbonized layer can provide additional lithium sources during the first charging process of the lithium-ion battery to compensate for the lithium ions lost during the formation of the SEI film, thereby effectively improving the first coulomb efficiency of the lithium-ion battery and improving the electrochemical performance of the negative electrode material and improving the rate performance. At the same time, during the charging and discharging process, the lithium nanoparticles can provide more active sites for lithium ions to react, thereby improving the electronic conduction performance. In addition, the lithium nanoparticles can fill the gaps in the polymerized carbonized layer, buffering the volume expansion of the silicon-carbon matrix, helping to maintain the integrity of the negative electrode material and inhibiting the pulverization of the silicon-carbon matrix.

[0043] Specifically, doping lithium nanoparticles in the polymerized carbonized layer by in-situ reduction can avoid the agglomeration or local enrichment of the lithium source, thereby effectively improving the dispersion uniformity of the lithium nanoparticles in the polymerized carbonized layer. At the same time, the lithium nanoparticles generated by in-situ reduction have better interface compatibility with the polymerized carbonized layer, thereby reducing the interface resistance and improving the structural stability of the lithium nanoparticles on the polymerized carbonized layer, thereby comprehensively improving the rate performance and cycle stability of the lithium-ion battery.

[0044] In some embodiments, the polymerized carbonized layer includes a connecting carbon skeleton and a coating carbon skeleton interconnected with the connecting carbon skeleton, and lithium nanoparticles are reduced and grown on the surface of the connecting carbon skeleton. In fact, the connecting carbon skeleton can be intertwined with the silicon-carbon skeleton in the silicon-carbon matrix, thereby improving the structural stability of the polymerized carbonized layer on the silicon-carbon matrix, thereby better adapting to the volume expansion changes of the silicon-carbon matrix during the charge and discharge process, preventing the polymerized carbonized layer from cracking and peeling off, and at the same time, after the coating carbon skeleton and the connecting carbon skeleton are interconnected, the position stability of the lithium nanoparticles on the surface of the connecting carbon skeleton can be improved, and the structural strength of the polymerized carbonized layer can be further improved, which is conducive to better adapting to volume changes.

[0045] In addition, the present invention also provides a method for preparing silicon-based negative electrode materials for lithium-ion batteries, comprising: coating a polymer on the surface of a silicon-carbon matrix after surface activation and impregnating it with an inorganic lithium salt before carbonization, reducing it under a hydrogen atmosphere and then coating the surface with organic matter and carbonizing it to obtain a silicon-based negative electrode material.

[0046] In fact, by pre-activating the surface of the silicon-carbon matrix, it is beneficial to introduce more functional groups on the surface of the silicon-carbon matrix, thereby improving the uniformity and stability of the polymer coating on the surface of the silicon-carbon matrix, and then forming a polymer coating layer on the surface of the silicon-carbon matrix. After impregnation with inorganic lithium salt, the inorganic lithium salt can enter the polymer coating layer, and after carbonization treatment, the polymer coating layer forms a connected carbon skeleton, and the inorganic lithium salt is solidified on the surface of the connected carbon skeleton, and then after reduction, lithium nanoparticles can be generated in situ. Finally, the surface is coated with organic matter and carbonized to form a polymer carbonized layer, and the lithium nanoparticles are encapsulated and fixed.

[0047] Specifically, see Figure 1 The preparation method provided by the present invention comprises the following steps:

[0048] S1, stirring and mixing the surface activated silicon-carbon matrix in an organic solution containing a polymer, and then separating and drying to obtain a composite matrix;

[0049] S2, mixing the composite matrix in an inorganic lithium salt solution, evaporating the solvent, and carbonizing at 300° C.-400° C. to obtain a composite intermediate;

[0050] S3, reducing the composite intermediate in a hydrogen atmosphere at 200° C.-300° C. to obtain a negative electrode intermediate;

[0051] S4. After the negative electrode intermediate is stirred and mixed in an organic solution, it is separated and dried, and carbonized at 700° C.-800° C. to obtain a silicon-based negative electrode material for a lithium-ion battery.

[0052] In some embodiments, see Figure 1When executing step S1, step S0 is performed in advance, the nano-silicon powder and the carbon precursor are mixed and ball-milled to obtain a silicon-carbon matrix, and the silicon-carbon matrix is ​​surface-treated in a silane solution to obtain a surface-activated silicon-carbon matrix. In fact, by mixing the nano-silicon powder and the carbon precursor by ball milling, the particle size of the carbon precursor can be effectively reduced and more active sites can be generated on the surface. Then, after calcination, the carbon precursor is carbonized to form a carbon skeleton and forms a silicon-carbon skeleton with the nano-silicon, thereby effectively improving the stability of the silicon-carbon matrix, which is beneficial to alleviate the volume change of silicon during the charge and discharge process.

[0053] Specifically, in step S0, the mass ratio of nano-silicon powder to carbon precursor is 1:(5-6), which is conducive to the carbon precursor to better wrap the nano-silicon powder during the ball milling mixing process, and then after calcination to form a silicon-carbon matrix, it can play a good coating and protection role for the nano-silicon powder. In addition, the relatively excessive carbon precursor can form a "carbon cage" structure after calcination and carbonization, which can accommodate the nano-silicon powder and limit the excessive expansion and contraction of silicon, thereby improving the structural stability of the silicon-carbon matrix.

[0054] Specifically, in step S0, the particle size of the nano silicon powder is 50nm-150nm, and the average particle size of the nano silicon powder is 100nm. In fact, small-sized silicon powder in the silicon-carbon skeleton is conducive to embedding and forming the silicon-carbon skeleton, and can be constrained by the silicon-carbon skeleton on a smaller scale when the volume changes, further avoiding the pulverization and cracking of the silicon-carbon material during the charge and discharge process. Specifically, the carbon precursor includes one of phenolic resin, asphalt, and glucose.

[0055] In some embodiments, when performing step S0, the nano-silicon powder and the carbon precursor are mixed and ball-milled at 100° C.-200° C. In fact, ball-milling in an environment of 100° C.-200° C. is conducive to improving the molecular activity of the nano-silicon powder and the carbon precursor, thereby promoting the carbon precursor to be wrapped on the surface of the nano-silicon powder and improving the uniformity of the wrapping, which is conducive to improving the dispersion uniformity of the nano-silicon powder in the silicon-carbon matrix and the stability of the silicon-carbon connection. Specifically, the nano-silicon powder and the carbon precursor are mixed and ball-milled for 8h-10h.

[0056] In some embodiments, when executing step S0, the nano-silicon powder and the carbon precursor are mixed and ball-milled, and then calcined at 700°C-1000°C to obtain a silicon-carbon matrix. In fact, during the high-temperature calcination process, the carbon precursor wrapped around the outside of the nano-silicon powder undergoes a carbonization reaction, thereby forming a carbon skeleton and coating the nano-silicon powder to form a composite silicon-carbon skeleton, which is conducive to forming a close interaction to enhance the structural stability of the silicon-carbon matrix and effectively buffer the volume change of silicon during the charge and discharge process. Specifically, after the silicon-carbon matrix is ​​obtained, the silicon-carbon matrix is ​​extruded and sieved to obtain a silicon-carbon matrix with a particle size of 50nm-100nm.

[0057] In some embodiments, when executing step S0, the solid-liquid ratio of the solid-liquid mixture formed by adding the silicon-carbon matrix to the silane solution is 0.05g / mL-0.08g / mL, which is conducive to promoting the uniform dispersion of the silicon-carbon matrix in the silane solution, thereby improving the full contact between the surface of the silicon-carbon matrix and the silane solution, thereby obtaining a full and uniform activation treatment, which is conducive to improving the consistency of the active groups on the surface of the silicon-carbon matrix, and is conducive to improving the uniformity of the subsequent polymer coating on the surface of the silicon-carbon matrix. Specifically, the mass ratio of the silane solute to the silicon-carbon matrix in the silane solution is (0.20-0.25):1.

[0058] In some embodiments, when performing step S0, the silane solute dissolved in the silane solution includes one of KH-550, KH-560, and KH-570. In fact, the active ingredient in KH-550 is γ-aminopropyltriethoxysilane, the active ingredient in KH-560 is γ-glycidyloxypropyltrimethoxysilane, and the active ingredient in KH-570 is γ-methacryloxypropyltrimethoxysilane.

[0059] In some embodiments, when executing step S0, the silicon-carbon matrix is ​​ultrasonically dispersed in a silane solution at 50° C.-60° C. This is conducive to the uniform distribution of the silicon-carbon matrix in the silane solution, and improves the activity of the silane solute in the silane solution, prompting the silane solute to perform surface modification treatment on the silane matrix, thereby effectively improving the treatment rate and uniformity of the surface of the silicon-carbon matrix.

[0060] In fact, in step S1, stirring and mixing the silicon-carbon matrix in the organic solution is conducive to the uniform coating of the polymer on the surface of the silicon-carbon matrix, and thus is conducive to the loading and embedding of the inorganic lithium salt by the polymer coating layer. Specifically, the polymer dissolved in the organic solution includes one of melamine, polypyrrole, and polyaniline. In fact, by selecting different polymers to coat the surface of the silicon-carbon matrix, different doping elements can be introduced, thereby effectively improving the interface performance between the polymer carbonized layer formed after the polymer carbonization and the silicon-carbon matrix.

[0061] In some embodiments, the solvent used in the organic solution in step S1 includes one of dimethyl sulfoxide, N,N-dimethylformamide, and dimethylformamide. In fact, the solvent of the organic solution can be a solvent commonly used in the art to dissolve the polymer used, and it is necessary that it does not react with the polymer and the silicon carbon matrix. Specifically, when preparing the organic solution, the polymer can be stirred and dissolved in the solvent using a dissolution method commonly used in the art, and it is necessary to form a uniform solution.

[0062] In some embodiments, the mass ratio of the silicon-carbon matrix after surface activation to the polymer in the organic solution in step S1 is 1:(0.1-0.3). In fact, after the silicon-carbon matrix is ​​added to the organic solution, the silicon-carbon matrix can serve as a matrix to coat the polymer on the surface of the silicon-carbon matrix, and by controlling the mass ratio of the silicon-carbon matrix to the polymer, the coating uniformity and coating thickness of the polymer on the surface of the silicon-carbon matrix can be adjusted, thereby controlling the thickness of the polymerized carbonized layer on the surface of the silicon-carbon matrix.

[0063] In some embodiments, in step S1, the surface activated silicon-carbon matrix is ​​placed in an organic solution at 45°C-55°C for ultrasonic mixing. In fact, by placing the silicon-carbon matrix in an organic solution at a certain temperature for ultrasonic treatment, it is not only beneficial to improve the dispersion uniformity of the silicon-carbon matrix in the organic solution, but also to promote the coating treatment of the polymer on the surface of the silicon-carbon matrix. Specifically, the organic solution can be preheated in a water bath environment at 45°C-55°C, and the surface activated silicon-carbon matrix can be preheated in an incubator at 45°C-55°C.

[0064] In fact, after the silicon-carbon matrix is ​​stirred and mixed in the organic solution in step S1, the solid-liquid separation is performed by vacuum filtration or filtration separation, and the separated solid is circulated and rinsed with anhydrous ethanol and deionized water, and then the obtained solid is dried in a vacuum drying oven at 50°C-70°C to constant weight to obtain a composite matrix. Specifically, by circulatory rinsing of the separated solid, it is beneficial to remove the polymer that is not completely adhered to the surface of the silicon-carbon matrix, and then after drying treatment, it is beneficial to improve the surface purity of the composite matrix and improve the adhesion stability of the polymer coating layer on the silicon-carbon matrix.

[0065] In some embodiments, the lithium solute in the inorganic lithium salt solution in step S2 includes one of lithium hydroxide and lithium hexafluoroarsenate. In fact, after the composite matrix is ​​added to the inorganic lithium salt solution, the inorganic lithium salt can penetrate into the polymer coating layer on the surface of the composite matrix, and after the solvent is evaporated, more inorganic lithium salt can be caused to enter or be coated on the surface of the composite matrix, thereby increasing the loading capacity of the composite matrix for lithium salt. In fact, when lithium hydroxide or lithium hexafluoroarsenate enters the polymer coating layer, it can interact with the polymer molecules, thereby improving the positional stability of the lithium salt in the polymer coating layer.

[0066] In fact, in step S2, the mass ratio of the composite matrix to the lithium solute in the inorganic lithium salt solution is 1: (0.08-0.12), and the solid-liquid ratio in the solid-liquid mixture formed after the composite matrix is ​​mixed with the inorganic lithium salt is 0.05g / mL-0.08g / mL. This is conducive to uniform loading of lithium solute on the surface of the composite matrix, and the appropriate solid-liquid ratio can promote uniform dispersion of the composite matrix in the initial stage, and is also conducive to subsequent solvent evaporation.

[0067] In some embodiments, in step S2, the composite matrix is ​​ultrasonically mixed in an inorganic lithium salt solution at 50° C. to 60° C. In fact, the ultrasonic cavitation effect of the ultrasonic wave can effectively promote the uniform dispersion of the composite matrix in the inorganic lithium salt solution, avoid agglomeration and sedimentation of the composite matrix, and the ultrasonic cavitation effect is also conducive to the lithium solute entering the polymer coating layer on the surface of the composite matrix.

[0068] Specifically, in step S2, the composite matrix is ​​mixed in an inorganic lithium salt solution, the solvent is evaporated, and the obtained solid is circulated and rinsed with deionized water, which is conducive to removing the excess lithium salt adhering to the surface of the composite matrix, thereby avoiding contamination of the silicon-based negative electrode material. In addition, after the solvent is evaporated and circulated, the obtained solid can be carbonized in a non-oxidizing atmosphere at 300°C-400°C, so that the polymer coating layer can be preliminarily carbonized and the lithium salt can be preliminarily fixed, which is conducive to improving the positional stability of the lithium salt during the reduction process. Specifically, the non-oxidizing atmosphere includes one of a nitrogen atmosphere and an inert atmosphere.

[0069] In some embodiments, after the solvent is evaporated in step S2, the obtained solid is transferred to an atmosphere furnace, and after the atmosphere furnace is filled with a non-oxidizing atmosphere, the furnace of the atmosphere furnace heats the solid at a rate of 1°C / min-10°C / min, and when the temperature is raised to 300°C-400°C, the solid is kept warm for 5h-6h for carbonization treatment, and the composite intermediate is obtained after cooling to room temperature with the furnace. In fact, the surface of the composite intermediate has a preliminarily carbonized connected carbon skeleton, and the connected carbon skeleton is anchored with a sintered and fixed lithium salt.

[0070] In fact, in step S3, the composite intermediate is heated to 200°C-300°C at a rate of 1°C / min-10°C / min in a hydrogen atmosphere and then kept warm for 2h-3h to in-situ reduce the lithium salt doped on the surface of the composite intermediate, thereby forming lithium nanoparticles on the surface of the connected carbon skeleton. Specifically, by controlling the heating rate of the composite intermediate in a hydrogen atmosphere, it is beneficial for the lithium salt to be uniformly reduced in the composite intermediate, thereby forming uniformly distributed lithium nanoparticles on the surface of the connected carbon skeleton, which helps to maintain the structural stability of the composite intermediate and improve the positional stability of the lithium nanoparticles on the surface of the connected carbon skeleton.

[0071] In some embodiments, when the negative electrode intermediate is stirred and mixed in the organic solution in step S4, the organic solvent used is the same as that in step S1, so that a polymer coating structure with the same properties can be formed on the surface of the negative electrode intermediate, thereby helping to improve the connection stability between the connected carbon skeleton and the coated carbon skeleton, and can also play a coating and protective role on the lithium nanoparticles, thereby improving the electrochemical performance stability of the negative electrode material during the cycle process.

[0072] In addition, the organic solution used in step S4 can reuse the organic solution remaining in step S2, or can be reconfigured. In fact, in the reconfiguration process, the solute of the organic solution used in step S4 is the same as that in step S2, and the concentration of the polymer solute is 0.5 times to 0.8 times that in step S2.

[0073] In some embodiments, in step S4, the negative electrode intermediate may be ultrasonically mixed in the organic solution to promote uniform loading of the polymer solute in the organic solution on the surface of the negative electrode intermediate, while preventing the negative electrode intermediate from agglomerating and settling. Specifically, the negative electrode intermediate may be ultrasonically mixed in the organic solution at 45° C. to 55° C. for 10 min to 15 min.

[0074] In some embodiments, in step S4, the negative electrode intermediate is stirred and mixed in an organic solution, and then separated by vacuum filtration and cyclic flushing with deionized water and anhydrous ethanol. The solid obtained by flushing is dried to constant weight in a vacuum drying oven at 40°C-55°C, and then transferred to an atmosphere furnace and heated to 700°C-800°C at a rate of 1°C / min-10°C / min for carbonization treatment for 3h-5h to obtain a lithium-ion battery silicon-based negative electrode material.

[0075] In fact, the present invention also provides an application of the silicon-based negative electrode material prepared by any of the above preparation methods in a lithium-ion battery. Specifically, the silicon-based negative electrode material can be mixed with a conductive agent and a binder to form a negative electrode slurry, and the negative electrode slurry is coated on a conductive current collector to form a negative electrode sheet, which is then assembled with a positive electrode, a separator, and an electrolyte to prepare a lithium-ion battery.

[0076] Example 1

[0077] This embodiment 1 provides a method for preparing a lithium-ion battery silicon-based negative electrode material, comprising the following steps:

[0078] S0. After mixing nano silicon powder with an average particle size of 100 nm and glucose in a mass ratio of 1:5, the mixture was put into a ball mill, zirconium oxide was used as the ball milling ball and the ball-to-material ratio was set to 20:1. After ball milling and blending at 150°C for 8 hours, the ball milling mixture was taken out and transferred to an atmosphere furnace. Under a nitrogen atmosphere, the temperature was raised to 800°C at a rate of 5°C / min, and then calcined for 2 hours and cooled to room temperature with the furnace to obtain a silicon-carbon matrix with an average particle size of 80 nm; the silicon-carbon matrix was added to an ethanol solution mixed with KH550 (the mass ratio of the silicon-carbon matrix to KH550 was 1:0.2) at a solid-liquid ratio of 0.06 g / mL, and ultrasonically mixed at 20 kHz for 15 minutes in a water bath environment at 55°C, filtered under reduced pressure and rinsed with deionized water, and dried in a vacuum drying oven to constant weight to obtain a surface-activated silicon-carbon matrix;

[0079] S1. Preheat the surface-activated silicon-carbon matrix in a vacuum drying oven at 55°C, then preheat an organic solution (solvent is dimethyl sulfoxide) dissolved with melamine (the mass ratio of the surface-activated silicon-carbon matrix to melamine is 1:0.2) in a water bath at 55°C, add the preheated silicon-carbon matrix into the organic solution, mix ultrasonically at a frequency of 20kHz for 15 minutes in a water bath at 55°C, keep warm for 5 minutes, filter under reduced pressure and wash, and then dry in a vacuum drying oven at 60°C to constant weight to obtain a composite matrix;

[0080] S2. The composite matrix taken out from the 60°C vacuum drying oven is added to an inorganic lithium salt solution dissolved with lithium hydroxide (the mass ratio of the composite matrix to lithium hydroxide is 1:0.1) at a solid-liquid ratio of 0.06 g / mL, and ultrasonically mixed in a 60°C water bath environment for 15 minutes. After the solvent is evaporated at 95°C, the obtained solid is rinsed with deionized water, and the solid is dried in a 55°C vacuum drying oven to constant weight, and then transferred to an atmosphere furnace. The atmosphere furnace is heated to 350°C at a rate of 5°C / min in a nitrogen atmosphere, and then kept warm for 5 hours, and then cooled to room temperature with the furnace to obtain a composite intermediate;

[0081] S3, transferring the composite intermediate to an atmosphere furnace, replacing the gas with hydrogen in the atmosphere furnace, heating the atmosphere furnace to 250°C at a rate of 5°C / min, and then keeping the temperature for 3 hours, and then cooling the furnace to room temperature to obtain a negative electrode intermediate;

[0082] S4. Add the negative electrode intermediate into the organic solution separated by vacuum filtration in step S2, carry out ultrasonic mixing in a 50°C water bath environment and keep warm for 30 minutes, remove the vacuum and use deionized water to rinse, dry to constant weight in a 50°C vacuum drying oven, transfer to an atmosphere furnace under a nitrogen atmosphere, heat to 800°C at a rate of 5°C / min, keep warm for carbonization treatment for 3 hours, and then cool to room temperature with the furnace to obtain a lithium-ion battery silicon-based negative electrode material.

[0083] Example 2

[0084] This embodiment 2 provides a method for preparing a silicon-based negative electrode material for a lithium-ion battery, which is different from the embodiment 1 in that the silicon-carbon matrix is ​​not subjected to surface activation treatment in step S0, and the silicon-carbon matrix is ​​directly preheated and then the organic solution is added in step S1.

[0085] Example 3

[0086] This embodiment 3 provides a method for preparing a silicon-based negative electrode material for a lithium-ion battery. The difference from embodiment 1 is that step S4 is not performed, and the silicon-based negative electrode material for a lithium-ion battery is prepared in step S3.

[0087] Example 4

[0088] This embodiment 4 provides a method for preparing a silicon-based negative electrode material for a lithium-ion battery, which is different from the embodiment 1 in that step S3 is not performed, and the composite intermediate obtained in step S2 is subjected to step S4.

[0089] Comparative Example 1

[0090] This comparative example 1 provides a method for preparing a silicon-based negative electrode material for a lithium-ion battery, which is different from Example 1 in that step S2 and step S3 are not performed, and the composite matrix obtained in step S1 is directly subjected to step S4.

[0091] Comparative Example 2

[0092] This comparative example 2 provides a method for preparing a silicon-based negative electrode material for a lithium-ion battery, which is different from that of example 1 in that steps S1 to S4 are not performed.

[0093] Performance Testing

[0094] The lithium-ion battery silicon-based negative electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were uniformly mixed with acetylene black and LA133 at a mass ratio of 8:1:1, respectively, and then coated on a copper foil. After being cut into composite sheets with a diameter of 14 mm, lithium sheets were used as positive electrode sheets, lithium hexafluorophosphate was used as electrolyte, and polypropylene microporous membranes were used as diaphragms. Button-type lithium batteries were assembled in a glove box, and the corresponding button-type lithium batteries in Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to cyclic charge and discharge tests at 25° C. and a rate of 0.2C. The results are shown in Table 1 below.

[0095] Table 1 Electrochemical performance test results of button lithium battery

[0096]

[0097] As can be seen from Table 1, the lithium ion battery using the silicon-based negative electrode material prepared in Example 1 has good capacity performance and cycle stability, and the capacity retention rate after 100 cycles is as high as 93.2%. In Example 2, the silicon-carbon negative electrode is not surface activated when preparing the negative electrode material, resulting in a decrease in the bonding performance between the silicon-carbon negative electrode surface and the polymerized carbonized layer, thereby resulting in a decrease in the cycle performance of the lithium ion battery. In Example 3, the lithium nanoparticles are not surface coated and carbonized when preparing the negative electrode material, resulting in a significant decrease in the cycle performance. In Example 4, the lithium salt is not in-situ reduced and the lithium salt is directly used for pre-lithiation, which affects the utilization rate of lithium and reduces the stability of lithium on the carbonized skeleton, thereby resulting in a decrease in the cycle performance.

[0098] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing a silicon-based negative electrode material for a lithium-ion battery, characterized in that: The following steps are involved: The nano-silicon powder and the carbon precursor are mixed and ball-milled in a mass ratio of 1:(5-6), and then calcined at 700°C-1000°C to obtain a silicon-carbon matrix; the silicon-carbon matrix is ​​surface-treated in a silane solution to obtain a surface-activated silicon-carbon matrix; the surface-activated silicon-carbon matrix is ​​stirred and mixed in an organic solution dissolved with a polymer, and then separated and dried to obtain a composite matrix; the composite matrix is ​​mixed in an inorganic lithium salt solution, the solvent is evaporated, and the composite intermediate is obtained after carbonization at 300°C-400°C; the composite intermediate is reduced in a hydrogen atmosphere at 200°C-300°C to obtain a negative electrode intermediate; the negative electrode intermediate is stirred and mixed in the organic solution, separated and dried, and carbonized at 700°C-800°C to obtain a lithium-ion battery silicon-based negative electrode material.

2. The preparation method according to claim 1, characterized in that: The particle size of the nano-silicon powder is 50nm-150nm; and / or, the carbon precursor includes one of phenolic resin, asphalt, and glucose; and / or, the nano-silicon powder and the carbon precursor are mixed and ball-milled at 100°C-200°C; and / or, the nano-silicon powder and the carbon precursor are mixed and ball-milled for 8h-10h; and / or, the particle size of the silicon-carbon matrix is ​​50nm-100nm.

3. The preparation method according to claim 1, characterized in that: The solid-liquid ratio of the silicon-carbon matrix to the silane solution is 0.05 g / mL-0.08 g / mL; and / or, the mass ratio of the silane solute in the silane solution to the silicon-carbon matrix is ​​(0.20-0.25):1; and / or, the silane solute in the silane solution includes one of KH-550, KH-560, and KH-570; and / or, the silicon-carbon matrix is ​​surface treated in a silane solution at 50° C.-60° C.; And / or, the silicon carbon matrix is ​​ultrasonically dispersed in the silane solution.

4. The preparation method according to claim 1, characterized in that: The mass ratio of the surface activated silicon carbon matrix to the polymer is 1:(0.1-0.3); and / or, the polymer includes one of melamine, polypyrrole, and polyaniline; and / or, the solvent in the organic solution includes dimethyl sulfoxide, N , N - one of dimethylformamide and dimethylformamide; and / or, ultrasonically mixing the surface activated silicon carbon matrix with an organic solution containing a polymer; and / or, stirring and mixing the surface activated silicon carbon matrix in an organic solution at 45°C-55°C.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the composite matrix to the lithium solute in the inorganic lithium salt solution is 1:(0.08-0.12); and / or, the lithium solute in the inorganic lithium salt solution includes one of lithium hydroxide and lithium hexafluoroarsenate; and / or, the solid-liquid ratio of the composite matrix to the inorganic lithium salt solution is 0.05g / mL-0.08g / mL; and / or, the composite matrix is ​​mixed in an inorganic lithium salt solution at 50°C-60°C; and / or, the composite matrix is ​​ultrasonically mixed in the inorganic lithium salt solution.

6. The preparation method according to claim 1, characterized in that: After mixing the composite matrix in an inorganic lithium salt solution, the solvent is evaporated and circulated and rinsed with deionized water; and / or, after evaporating the solvent, carbonization is performed in a non-oxidizing atmosphere at 300°C-400°C, wherein the non-oxidizing atmosphere includes a nitrogen atmosphere and an inert atmosphere; and / or, after evaporating the solvent, the temperature is increased to 300°C-400°C at a rate of 1°C / min-10°C / min; and / or, after evaporating the solvent, carbonization treatment is performed at 300°C-400°C for 5h-6h.

7. The preparation method according to claim 1, characterized in that: The composite intermediate is heated to 200-300° C. at a rate of 1° C. / min-10° C. / min in a hydrogen atmosphere; and / or, the composite intermediate is kept warm for 2 h-3 h in a hydrogen atmosphere.

8. A silicon-based negative electrode material obtained by the preparation method according to any one of claims 1 to 7.

9. Use of the silicon-based negative electrode material prepared by the preparation method according to any one of claims 1 to 7 in a lithium-ion battery.

Citation Information

Patent Citations

  • Method for preparing silicon carbide alloy negative electrode material for lithium ion battery

    CN102376944A

  • Preparation method of silicon based negative electrode material of lithium ion battery

    CN110844910A

  • Pre-lithiated silicon monoxide / carbon composite material, and preparation method and application thereof

    CN112289999A